Recherche sur l'activite anthelmintique des plantes de l'Afrique de l'Ouest - Ibrahim, M.A.; Nwude, N.; Ogunsusi, R.A.; Aliu, Y.O. (1984)
Eighteen plants traditionally used for the treatment of human and animal helminthiasis in Africa were screened for anthelmintic activity using the Nippostrongylus - rat model. Aloe barteri, Terminalia avicennioides, Annona senegalensis, Cassia occidentalis, Anogeissus leiocarpus and Diospyros mespiliformis showed significant activity, giving deparasitizations of 92, 89, 75, 69, 60 and 58% respectively compared to untreated controls.